Estrutura organizacional da atividade apícola nos municípios de Silvânia, Vianópolis e Orizona, Goiás - Visconde, José Vieira (2016)
This research aimed to analyze the organizational structure of the beekeeping activity in the municipalities of Goiás, Silvânia, Vianópolis and Orizona. The research was carried out during February 2016. Data on the conditions of the organizational structure of the beekeeping activity in these three municipalities were collected and analyzed. Semi-structured questionnaires were applied to 28 beekeepers. Questionnaires included questions on social organizational structure, economic organization structure, technological organizational structure, environmental organizational structure and the organizational structure of management. To meet the proposed objectives, the study is based ona literature review, documental research, interviews, application of semi-structured questionnaires and quantitative and qualitative analysis of data from field research. It was shown, that most beekeepers do not adopt good management practices in their business. They do not have an organizational structure that allows produce honey with safety and quality. An organizational structure guided by traditional schemes, with few technologies and maintenance of beekeeping as a secondary activity, has not proved sufficient to achieve and / or sustain competitiveness with other Brazilian states.